Analysis of Risk Management in the Josua Fashion Business Jalan Pancing Medan - Nainggolan, Ruly Manuel; Liany, Aprilia Putri; Hutagaol, Maceru; Frederic, Yosep Bonar; Ramadhan, Jizdan (Economic: Journal Economic and Business, 2024)
This research was conducted at one of the MSMEs operating in the fashion sector, called Josua Fashion, where the researcher focused on analyzing risk management that occurred in this business. Data collection used in this research used qualitative research methods. Namely, the method is applied by conducting interviews with business owners Josua Fashion in Medan City Literacy Tax. This research was conducted on June 7 2024. The interview was conducted with the aim of obtaining information for data collection, and knowing the seller's perception or opinion regarding risk management in this business and also knowing the strategy of this business in mapping, predicting and seeing what possible risks are. what will happen and formulate what management strategies need to be applied to the business